Protists and nematodes improve assessment of soil multifunctionality recovery in Suaeda salsa remediated saline soils - Ayijiamali Kudureti; Haidong Gu; Shuai Zhao; Bin Peng; Xu Liu; Baozhan Wang; Yu Shi; Hazaisi Hanipa; Zhenyong Zhao; Changyan Tian; Guanghui Lv (Applied Soil Ecology, 2026)

Biochar and iron minerals facilitate the reduction of pollution and sequestration of carbon in chloramphenicol-contaminated soil under dry conditions - Pengfei Cheng; Junliang Chen; Ran Xu; Qin Tian; Xiaobo Luo; Zhicong Dai; Zhiliang Li; Yao Lu; Lianghui Li; Kuan Cheng; Chao Guo; Guanlin Li; et al. (Applied Soil Ecology, 2025)

Microbial community assembly elucidates differential biotic homogenization in soils caused by agricultural expansion in the Yangtze River estuary - Yufan Yang; Yanhan Ji; Shuying Wang; Congrui Liu; Ping Zhang; Guifeng Gao; Yu Shi; Jiandong Jiang; Xu Liu; Baozhan Wang (Applied Soil Ecology, 2025)

Effects of reduced pH and elevated pCO 2 on sperm motility and fertilisation success in blood clam, Tegillarca granosa - Wei Shi; Xinguo Zhao; Yu Han; Cheng Guo; Saixi Liu; Wenhao Su; Yichen Wang; Shanjie Zha; Xueliang Chai; Wandong Fu; Huicheng Yang; Guangxu Liu (New Zealand Journal of Marine and Freshwater Research, 2017)
Although it has been shown that ocean acidification generally has a negative impact on fertilisation success of broadcast spawning marine organisms, whether induced fertilisation success reduction is a consequence of elevated p CO 2 or decreased pH remains unclear. Therefore, the impacts of HCl‐ and CO 2 ‐induced acidified seawater on sperm motility and gametes fertilisation capability of a broadcast spawning bivalve species, Tegillarca granosa were investigated in the present study. The results showed that the fertilisation capability of both gametes was significantly reduced in either HCl‐ or CO 2 ‐acidified seawater. In addition, significant impacts on sperm motility were observed in the group exposed to CO 2 ‐acidified seawater, suggesting that this parameter is sensitive to p CO 2 instead of solely pH value. The differences between the two seawater acidification manipulating methods may be due to the intrinsic difference in diffusion capability of CO 2 and protons.